A comunicação pública no contexto de uma emissora controlada pelo estado: estudo de caso da Televisão Brasil Central - Freitas, Denyse Parreira de Deus Araújo (2016)
This research work is a case study of the broadcaster Televisão Brasil Central (TBC), whose concession belongs to the government of the State of Goiás. The objective was, from the local television news content analysis, investigate the possibilities of the practice of public communication in a station maintained by public funds and managed by the State. Therefore, the research also focused on the investigation of the operating characteristics and station management through the analysis of official documents, in order to verify the existence (or not) conditions or elements that could qualify it as public broadcaster. The theoretical framework was built by bibliographic research by discussing topics such as the concept of public communication and its relationship to citizenship and the right to communication, legal aspects about the Brazilian sounds and images broadcasting system, public television in Brazil and Latin America and television journalism. The analysis of official documents revealed the absence of legal provisions that assign the operation of the station with educational and cultural goals and propitiate participation and control by society. Content analysis revealed predominantly factual and local news coverage. Most news with direct or indirect mention of the state government had a favorable approach to the government, although it was possible to identify the disclosure issues with unfavorable approach to current government.